2011
DOI: 10.1163/017353711x587741
|View full text |Cite
|
Sign up to set email alerts
|

Multiple paternity in the Black Caiman (Melanosuchus niger) population in the Anavilhanas National Park, Brazilian Amazonia

Abstract: The formation of dominance hierarchies in which the female mates with a large dominant male is common among crocodilians. However, there is the possibility of polyandry, in which females mate with multiple partners during a single breeding season and generate offspring with multiple paternity. In the present study, eight pairs of heterologous primers developed for Alligator mississippiensis and Caiman latirostris were used to determine whether multiple paternity exists in the Black Caiman, Melanosuchus niger. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Crocodilians, which have widely varying population densities and degrees of male territoriality, provide an excellent system to explore the evolutionary and ecological drivers that underlie the observed variation in the frequency of multiple paternity (Amavet, Rosso, Markariani, & Piña, 2008;Budd, Spotila, & Mauger, 2015;Davis, Glenn, Elsey, Dessauer, & Sawyer, 2001;Lance et al, 2009;Lewis, FitzSimmons, Jamerlan, Buchan, & Grigg, 2013;Mcvay et al, 2008;Muniz et al, 2011;Ojeda, Amavet, Rueda, Siroski, & Larriera, 2017;Oliveira, Marioni, Farias, & Hrbek, 2014;Lafferriere et al, 2016;Wu & Hu, 2010). The frequency of multiple paternity observed across crocodilian taxa ranges from 32% in the Chinese alligator (Alligator sinensis) to 100% in black caiman (Melanosuchus niger) (Muniz et al, 2011;Wu & Hu, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crocodilians, which have widely varying population densities and degrees of male territoriality, provide an excellent system to explore the evolutionary and ecological drivers that underlie the observed variation in the frequency of multiple paternity (Amavet, Rosso, Markariani, & Piña, 2008;Budd, Spotila, & Mauger, 2015;Davis, Glenn, Elsey, Dessauer, & Sawyer, 2001;Lance et al, 2009;Lewis, FitzSimmons, Jamerlan, Buchan, & Grigg, 2013;Mcvay et al, 2008;Muniz et al, 2011;Ojeda, Amavet, Rueda, Siroski, & Larriera, 2017;Oliveira, Marioni, Farias, & Hrbek, 2014;Lafferriere et al, 2016;Wu & Hu, 2010). The frequency of multiple paternity observed across crocodilian taxa ranges from 32% in the Chinese alligator (Alligator sinensis) to 100% in black caiman (Melanosuchus niger) (Muniz et al, 2011;Wu & Hu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Crocodilians, which have widely varying population densities and degrees of male territoriality, provide an excellent system to explore the evolutionary and ecological drivers that underlie the observed variation in the frequency of multiple paternity (Amavet, Rosso, Markariani, & Piña, 2008;Budd, Spotila, & Mauger, 2015;Davis, Glenn, Elsey, Dessauer, & Sawyer, 2001;Lance et al, 2009;Lewis, FitzSimmons, Jamerlan, Buchan, & Grigg, 2013;Mcvay et al, 2008;Muniz et al, 2011;Ojeda, Amavet, Rueda, Siroski, & Larriera, 2017;Oliveira, Marioni, Farias, & Hrbek, 2014;Lafferriere et al, 2016;Wu & Hu, 2010). The frequency of multiple paternity observed across crocodilian taxa ranges from 32% in the Chinese alligator (Alligator sinensis) to 100% in black caiman (Melanosuchus niger) (Muniz et al, 2011;Wu & Hu, 2010). Among crocodilians, it is not clear if the frequency of multiple paternity is driven by population density and/or mate encounter rate (Amavet et al, 2008;Budd et al, 2015;Davis et al, 2001;Lance et al, 2009;Lewis et al, 2013;McVay et al, 2008;Muniz et al, 2011;Oliveira et al, 2014;Lafferriere et al, 2016;Wu & Hu, 2010) though both have been suggested (Budd et al, 2015;Lafferriere et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyandry might be beneficial to females as it increases the genetic variability of their offspring (Yasui, 1998). Multiple paternity has been detected in both species subjected to heavy hunting in the Amazon basin (Muniz et al, 2011;Oliveira, Farias, Marioni, Campos, & Hrbek, 2010;Oliveira, Marioni, Farias, & Hrbek, 2014).…”
Section: Genetics and Ecology Of Caiman Populationsmentioning
confidence: 99%
“…Another of the mechanisms that facilitates the resilience of crocodilian populations to overhunting might be found in their mating system. Multiple paternity increases effective population size by maintaining genetic variation, and therefore acting as an important mechanism to preserve genetic diversity in isolated local populations (Chesser & Baker, 1996;Muniz et al, 2011;Rafajlovi c et al, 2013).…”
Section: Genetics and Ecology Of Caiman Populationsmentioning
confidence: 99%